PENGARUH STRATEGI STAD PADA PEMBELAJARAN BIOLOGI TERHADAP KETERAMPILAN PROSES SAINS SISWA SMA DI KOTA METRO - Muhfahroyin, Muhfahroyin (UNIVERSITAS MUHAMMADIYAH METRO, 2010)
The objectives of this research are to know the effect of STAD strategy toward the science process skills on different academic ability. This research was conducted at Senior High School students in Metro City, by using pretest-posttest nonequivalent control group design with factorial 2 x 2. The data was analysed by Ancova test. Based on the data analysis and discussion of this research show that there was an effect of STAD strategy toward the science process skills students, there was no a different between high and low ability students, there was no an effect of STAD strategy and academic ability interaction toward the science process skills students. Based on the result of this research, the researcher suggests that biology teachers in Metro City can be implemented the STAD strategy in biology learning to increasing science process skills students.Kata kunci: Keterampilan Proses Sains, STAD.